Archiwum klonów starych drzew sosny zwyczajnej w Puszczy Augustowskiej - Korczyk, Adolf; Myszczyńska, Izabela (Leśne Prace Badawcze, 2012)
Prior to 1800 no artificial regeneration or planting took place in the Augustowska Forest, therefore any trees currently more than 200 years come, genetically, from the native population. For preservation the gene resources such trees one ceated the clone archive. Between 1986 and 1990, 92 pine trees of 200-years old or more were inventoried: this census included 26 trees from fresh-coniferous forest habitat, 54 trees from fresh-mixed-coniferous forest habitat, and 12 trees from fresh-mixed-broadleaved forest habitat. These trees were vegetatively propagated to create a clone bank by grafting current the years’ shoots onto 2-year-old rootstocks. Two clone banks containing grafted strains of 60 native pines were planted in 1999 in the Augustowska Forest, Pomorze Forest District: BG-So-P1 located in compartment 637d, and BG-So-P2 and BG-So-P3 both in compartment 960a,b. Eleven years after planting out, the survival rate of 13-year old pine clones was: 79 % in the BG-So-P1, 63 % in BG-So-P2 and 86% in BG-So-P3. An evaluation of seed-bearing trees revealed differences among banks of these 13-year old clones. In BG-So-P1, were fruiting was plentiful (70%); but in BG-So-P3 17% of the clones bore seeds, and in BG-So-P2 only 3% of the clones bore seeds.